Requirements Engineering of Village Innovation Application Using Goal-Oriented Requirements Engineering (GORE) - Condro Kartiko; Ariq Cahya Wardhana; Wahyu Andi Saputra (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
The delay in the absorption of village funds from the central government to the village government is due to the village government's difficulty preparing village development innovation programs. The innovation tradition will grow if the cycle of transformation of knowledge and acceptable practices from one village to another, especially villages with similar conditions and problems, can run smoothly. For the process of exchanging knowledge and experiences between villages to run smoothly, it is necessary to codify best practices in a structured, documented, and disseminated manner. This research aims to design an application that functions as a medium for sharing knowledge about the use of village funds through government innovation narratives. The application is expected to become a reference for villages to carry out innovative practices by conducting replication studies and replicating acceptable practices that other villages have done. Therefore, it is necessary to have a system requirements elicitation method that can explore the village's requirements in sharing knowledge so that the resulting system is of high quality and by the objectives of being developed. There are several Goal-Oriented Requirements Engineering (GORE) methods used, such as Knowledge Acquisition in Automated Specification (KAOS) and requirements engineering based on business processes. In this research, the KAOS method was demonstrated as the elicitation activity of a village innovation system. Then the results were stated in the Goal Tree Model (GTM). Model building begins with discussions with the manager of the village innovation program to produce goals. The goals are then broken down into several sub-goals using the KAOS method. The KAOS method is used for the requirements elicitation process resulting in functional and non-functional requirements. This research is the elicitation of the requirement for the village innovation system so that it can demonstrate the initial steps in determining the requirements of the village innovation system before carrying out the design process and the system creation process. The results of this requirement elicitation can be used further in the software engineering process to produce quality and appropriate village innovation applications.